Paddy straw management practices in Northern India for improved efficiency and techno-economic feasibility - DHANGER, PARVEEN; JAIN, MUKESH; RANI, VIJAYA; KUMAR, MOHIT; GHANGHAS, SACHIN (The Indian Journal of Agricultural Sciences, 2022)
The study deals with the optimization of paddy residue management technologies for the management of paddy straw in combine harvested fields. The study emphasizes paddy straw management under different techniques (Retention, Incorporation and Removal of straw) with the use of different combinations of machinery. The research was conducted at farmer's field Dabra, Hisar, Haryana during 2017–18. The objective of the research was to evaluate techno-economic feasibility of different options of machinery. According to the results of the trials, the M4 (Combine harvester with SMS + Reversible mould board plough + Rotavator + Seed drill) had the greatest fuel consumption of 53.12 l/ha. M2 (Combine harvester with SMS + Spatial till drill) had the lowest fuel consumption of 22.29 l/ha. The lowest cost of operation of 63.32 `/q was found in treatment M2. Highest unit cost operation of 140.52 `/q was found in M9 (Traditional combine + Stubble shaver + Hay rake + Straw baler + Disc harrow (2 pass) + Planker + Seed drill). The benefit-cost ratio was found to be highest in traditional combine (1.99) and lowest in zero-till drill (1.11). Treatment-wise, benefit-ratio ratio was found maximum in treatment M10 (1.80) and minimum in M5 (1.50). According to the findings of study, residue retention technology is found better in comparison to straw incorporation and straw removal.